2022
DOI: 10.1530/rep-22-0123
|View full text |Cite
|
Sign up to set email alerts
|

Early growth response 1 transcription factor is essential for the pathogenic properties of human endometriotic epithelial cells

Abstract: Although a benign gynecological disorder, endometriosis displays some pathogenic features of malignancy, such as cell proliferation, migration, invasion, and adaptation to hypoxia. Current treatments of endometriosis include pharmacotherapy and/or surgery, which are of limited efficacy and often associated with adverse side-effects. Therefore, to develop more effective therapies to treat this disease, a broader understanding of the underlying molecular mechanisms that underpin endometriosis needs to be attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Collectively, our genetic, protein, and phenotypic analysis in this short technical report demonstrates that the Egr1 f/f allele operates as designed and therefore will be of significant utility for researchers interested in resolving EGR1 responses at a tissue and/or cell‐type specific level. For example, we have recently demonstrated that EGR1 is critical for both normal and abnormal uterine function (Maurya et al, 2022; Park et al, 2021; Szwarc et al, 2019). As EGR1 is expressed in endometrial epithelial and stromal cells (Maurya et al, 2022; Park et al, 2021; Szwarc et al, 2019), selective ablation of the EGR1 in the epithelial or stromal‐specific cell type will provide an unprecedented opportunity to investigate EGR1's role in endometrial biology and pathobiology at a cell‐type specific level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, our genetic, protein, and phenotypic analysis in this short technical report demonstrates that the Egr1 f/f allele operates as designed and therefore will be of significant utility for researchers interested in resolving EGR1 responses at a tissue and/or cell‐type specific level. For example, we have recently demonstrated that EGR1 is critical for both normal and abnormal uterine function (Maurya et al, 2022; Park et al, 2021; Szwarc et al, 2019). As EGR1 is expressed in endometrial epithelial and stromal cells (Maurya et al, 2022; Park et al, 2021; Szwarc et al, 2019), selective ablation of the EGR1 in the epithelial or stromal‐specific cell type will provide an unprecedented opportunity to investigate EGR1's role in endometrial biology and pathobiology at a cell‐type specific level.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we have recently demonstrated that EGR1 is critical for both normal and abnormal uterine function (Maurya et al, 2022; Park et al, 2021; Szwarc et al, 2019). As EGR1 is expressed in endometrial epithelial and stromal cells (Maurya et al, 2022; Park et al, 2021; Szwarc et al, 2019), selective ablation of the EGR1 in the epithelial or stromal‐specific cell type will provide an unprecedented opportunity to investigate EGR1's role in endometrial biology and pathobiology at a cell‐type specific level. In closing, it should be noted that the use of an Egr1 f/f mouse was recently reported by a research group in China (Lei et al, 2022; Wu et al, 2018, 2019); however, details on how this mouse was generated or whether the mouse will be made available to the scientific community has not been published.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome scale RNA‐sequencing (RNA‐seq) and analysis were performed as previously described 31,32 . Briefly, total RNA purity and physical integrity were determined using the NanoDrop spectrophotometer (ThermoFisher Scientific Inc.) and the 2100 Bioanalyzer with RNA chips (Agilent Technologies Inc., Santa Clara, CA), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Genome scale RNA-sequencing (RNA-seq) and analysis were performed as previously described. 31,32 Briefly, total RNA purity and physical integrity were determined using the NanoDrop spectrophotometer (ThermoFisher Scientific Inc.) and the 2100 Bioanalyzer with RNA chips (Agilent Technologies Inc., Santa Clara, CA), respectively. Total RNA preparations that scored a RNA integrity number (RIN) of 7 or greater were used in these experiments; RNA samples from three mice were used for each genotype.…”
Section: Genome-wide Rna Expression Profilingmentioning
confidence: 99%